A p‐Hydroxyphenacyl–Benzothiazole–Chlorambucil Conjugate as a Real‐Time‐Monitoring Drug‐Delivery System Assisted by Excited‐State Intramolecular Proton Transfer. Issue 13 (25th February 2016) - Barman, Shrabani; Mukhopadhyay, Sourav K.; Biswas, Sandipan; Nandi, Surajit; Gangopadhyay, Moumita; Dey, Satyahari; Anoop, Anakuthil; Pradeep Singh, N. D.
Abstract: Among the well‐known phototriggers, the p ‐hydroxyphenacyl (pHP) group has consistently enabled the very fast, efficient, and high‐conversion release of active molecules. Despite this unique behavior, the pHP group has been ignored as a delivery agent, particularly in the area of theranostics, because of two major limitations: Its excitation wavelength is below 400 nm, and it is nonfluorescent. We have overcome these limitations by incorporating a 2‐(2′‐hydroxyphenyl)benzothiazole (HBT) appendage capable of rapid excited‐state intramolecular proton transfer (ESIPT). The ESIPT effect also provided two unique advantages: It assisted the deprotonation of the pHP group for faster release, and it was accompanied by a distinct fluorescence color change upon photorelease. In vitro studies showed that the p ‐hydroxyphenacyl–benzothiazole–chlorambucil conjugate presents excellent properties, such as real‐time monitoring, photoregulated drug delivery, and biocompatibility. Abstract : Let it go… The two major limitations for theranostics of the p ‐hydroxyphenacyl (pHP) phototrigger were overcome by incorporating a benzothiazole appendage to enable rapid excited‐state intramolecular proton transfer (ESIPT; see picture). The ESIPT effect had two key advantages: It assisted the deprotonation of pHP group for faster release of the anticancer drug chlorambucil and led to a fluorescence color change upon photorelease.